The Effectiveness of Video-Based Media in Improving Understanding of Clean and Healthy Living Behavior for Diarrhea Prevention among Elementary School Students - Ardela, Mirna; Hiryadi; Ariadi, Herman; Ra’uf, Muhammad (Fakultas Kedokteran, Universitas Papua, 2025)
Diarrhea remains a public health problem among elementary school children and is closely associated with the low implementation of Clean and Healthy Living Behavior (CHLB). Health education is an important effort in diarrhea prevention; however, conventional methods are often less engaging for children. This study aimed to analyze the effectiveness of video-based media in improving students’ understanding of CHLB as an effort to prevent diarrhea among students at Kelayan Timur 13 Public Elementary School, Banjarmasin. This study employed a quantitative method using a pre-experimental one-group pre-test–post-test design. The study population consisted of 82 students from grades III to VI, selected using a total sampling technique. Students’ understanding of CHLB was measured using a questionnaire that had been tested for validity and reliability before and after the educational intervention delivered through video-based media. Data were analyzed using the Wilcoxon matched-pairs test. The results showed a significant improvement in students’ understanding after the educational intervention. Prior to the intervention, students’ understanding ranged from poor to good, whereas after the intervention, all respondents (100%) achieved a good level of understanding. Statistical analysis revealed a significant difference between pre-test and post-test scores (p = 0.001). It can be concluded that education on CHLB delivered through video-based media is effective in improving elementary school students’ understanding for diarrhea prevention.